(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstrak: The research was conducted on the basis of initial observations location study indicated that employee performance is still relatively low. The relatively low performance of employees is presumably related to the implementation of human relations factors in the work environment at the Regional Employment Board of West Halmahera. Thus, this study aims to: (1) to investigate the implementation of human relations approach. (2) To determine the achievement of employee performance. (3) To analyze the effect of the implementation of human relations approach to employee performance at the Regional Employment Board West Halmahera district. By applying the method of descriptive and quantitative approach, respondents were determined purposively sampled as many as 53 employees, then distributed a list of questions or the questionnaire, the results are tabulated and analyzed by applying statistical techniques. To describe the research variables used analytical technique that is processed in the percentage of Frequency Distribution Table, while to test the hypothesis used a simple linear regression analysis and correlation of product moment. Once the data is collected and then analyzed the results showed that (1) Implementation of human relations approach in working condition at the Regional Personnel Agency (BKD) West Halmahera has succeeded in improving the performance of employees that are in the category of "high". (2) The increased performance of employees at local staffing agency West Halmahera succession is determined or influenced by the application of human relations approach in working condition. Thus, it can be concluded that the hypothesis which states that "the human relations approach effect on Employee Performance in the Regional Employment Board of West Halmahera District", acceptable empirically at the same time justifying the underlying theories. Can be given some suggestions as follows: (1) To optimize employee performance, it is recommended to local governments West Halmahera streamline performance benefits are selective and controlled in order to avoid wastage of financial areas, as well as boost employee performance itself. (2) In addition, the application of human relations approach is needed more fused with a bureaucratic culture that is based on the culture and local wisdom to better work together in encouraging employee performance more optimally. Keywords: Approach Human Relations, Employee Performance